Pancreatic pseudocyst as a cause for gastric outlet obstruction. Issue 3 (17th March 2023) - Suleman, Mujaheed; Tadayo, Joshua; Tendwa, Irene; Amsi, Patrick; Tsandiraki, Justin; Lodhia, Jay
Abstract: The pancreatic pseudocyst contains pancreatic enzymes encapsulated by a non‐epithelialized wall. They are rare in the pediatric population and are mostly a result of pancreatic trauma: extrinsic, or intrinsic. Management options include conservative or surgical, depending on the clinical signs and symptoms, and the size of the cyst.